1975
DOI: 10.1177/002202217562002
|View full text |Cite
|
Sign up to set email alerts
|

Concrete Operational Development in Three Cultures

Abstract: Berry's (1971) model of ecological functionalism is extended to Piagetian developmental psychology. It is predicted that the rate of development of concrete operations may be partly determined by ecological and cultural factors. In particular, if three subsistence-economy populations are placed on an ecocultural scale, with low food-accumulating, nomadic, hunting groups at one extreme, and high food-accumulating, sedentary, agricultur-alist groups at the other extreme, the former are expected to develop spatia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
3

Year Published

1980
1980
2019
2019

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(41 citation statements)
references
References 6 publications
0
38
0
3
Order By: Relevance
“…It seems that even in a fairly acculturated community, the traditional value orientations that determine child rearing practices remain unchanged for a long time; in his research with more traditional groups of Australian Aborigines, Dasen ( , 1975) also attributed the slow acquisition of conservation concepts, relative to the spatial domain, to the value placed on spatial skills rather than on quantification.…”
Section: Harford (Boulton-lewis Neil1 and Harford In Press)mentioning
confidence: 99%
“…It seems that even in a fairly acculturated community, the traditional value orientations that determine child rearing practices remain unchanged for a long time; in his research with more traditional groups of Australian Aborigines, Dasen ( , 1975) also attributed the slow acquisition of conservation concepts, relative to the spatial domain, to the value placed on spatial skills rather than on quantification.…”
Section: Harford (Boulton-lewis Neil1 and Harford In Press)mentioning
confidence: 99%
“…The cognitive apparatus of humans develops on the basis of experiences that are processed within the ecocultural context [cf. also Dasen, 1975;Serpell, 1979;Jahoda, 1982]. Competence as stressing primarily social skills grows in contexts where cooperation among the members of the family is crucial for surviving.…”
Section: Introductionmentioning
confidence: 99%
“…Another line of research which has shown a relation between ecocultural demands and performance on cognitive and perceptual tasks is that of Dasen (1975Dasen ( , 1977. This study used Piaget's tests of spatial concepts and conservation and found "the structural properties of the stages and their hierarchical ordering were verified in each sample'' (Dasen 1977: 190), while cross-cultural variations in the average age at which the stages were attained in different domains were predictable from a functional analysis of the eco-cultural settings.…”
Section: Resultsmentioning
confidence: 99%